2021
DOI: 10.1182/blood.2020007848
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study of inotuzumab ozogamicin in pediatric relapsed/refractory acute lymphoblastic leukemia (ITCC-059 study)

Abstract: This Phase I study investigated the recommended Phase II dose (RP2D) of inotuzumab ozogamicin (InO), a CD22-directed antibody-drug conjugate, in pediatric patients with multiple-relapsed/refractory (R/R) CD22-positive acute lymphoblastic leukemia (ALL). Patients (≥1-<18 years) received three InO doses (Days 1, 8, 15) per course. Dose-escalation was based on dose-limiting toxicities (DLT) during Course 1 . Dose level 1 (DL1)=1.4 mg/m2 (0.6-0.4-0.4 mg/m2); DL2=1.8 mg/m2 (0.8-0.5-0.5 mg/m2). Secondary endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 33 publications
4
41
0
5
Order By: Relevance
“…Additionally, it is recommended to use prophylactic pharmacologic agents (e.g., ursodiol), to limit the inotuzumab use to two cycles if HCT is planned, and to avoid HCT conditioning regimens that contain dual alkylating agents (e.g., thiotepa and melphalan) and concomitant hepatotoxic drugs (e.g., azoles) [ 152 ]. In a pediatric phase I study that used fractionated weekly dosing for relapsed/refractory B-ALL, complete remission was seen in 80% of the patients and 84% of those with available flow cytometry data had negative MRD [ 153 ].…”
Section: Emerging Therapy: Immunotherapymentioning
confidence: 99%
“…Additionally, it is recommended to use prophylactic pharmacologic agents (e.g., ursodiol), to limit the inotuzumab use to two cycles if HCT is planned, and to avoid HCT conditioning regimens that contain dual alkylating agents (e.g., thiotepa and melphalan) and concomitant hepatotoxic drugs (e.g., azoles) [ 152 ]. In a pediatric phase I study that used fractionated weekly dosing for relapsed/refractory B-ALL, complete remission was seen in 80% of the patients and 84% of those with available flow cytometry data had negative MRD [ 153 ].…”
Section: Emerging Therapy: Immunotherapymentioning
confidence: 99%
“…Our cohort showed a lower MRD‐negativity rate compared both to the adult and the available paediatric data in older children treated with InO 4–7 . No descriptive results of the three patients aged 2–4 years were included in the retrospective cohort published by Bohjwani; one KMT2A ‐r patient in the ITCC‐059 cohort achieved CR and at relapse 7% of the blasts were CD22‐negative 6,9 …”
Section: Discussionmentioning
confidence: 74%
“…Phase I–II trials with InO in paediatric R/R ALL did not include infants 4,5 . Paediatric results with InO reflect the positive experience reported in adults, with response rates ranging from 58% to 80%, and the majority of responders becoming MRD‐negative (65–84%) 4–7 …”
Section: Introductionmentioning
confidence: 92%
“…In another cohort including children with r/r ALL treated with InO only one IFD was recorded (2%), while severe neutropenia was estimated at 44.9% [ 76 ]. A recent phase I study of InO in pediatric r/r ALL reported neutropenia in 56% of treated children, but low severe infection rates (8%; one with lung infection and one with sepsis after AHSCT) [ 77 ]. A retrospective study of r/r precursor B-cell ALL in pediatric patients under compassionate use with InO and blinatumomab recorded two severe infections (6.5%) that led to death [ 78 ].…”
Section: Targeting Antigens On Lymphoid Cellsmentioning
confidence: 99%